Retinal vein occlusion – pathomechanisms with a special focus on younger patients - Wojciech Zawisza (Klinika Oczna)
Retinal vein occlusion is one of the most common eye conditions and leads to significant visual impairment. Treatment does not always improve the acuity of vision, hence it is important to understand the prothrombotic pathomechanisms underlying the condition. The aim of this review is to outline key information regarding the factors contributing to the development of retinal vein occlusion, focusing specifically on the group of younger patients.